The Amazing Spider-Man Collection: The Amazing Spider-Man & The Amazing Spider-Man 2 - Field, Sally; Sheen, Martin; Khan, Irrfan; Scott, Campbell; 1967-2020; Zylka, Chris; 1966-; 1985-; Horner, James; Lee, Stan; 1922-2018.; Ditko, Steve; et al. (Culver City, Calif., 2012)
Peter Parker finds a clue that might help him understand why his parents disappeared when he was young. His path puts him on a collision course with Dr. Curt Connors, his fathers former partner.
Keywords: Drama; (Fictitious character); Spider-Man; Heroes; Drama; Fathers and sons; Drama